Private Security and the State in Latin America: The Case of Mexico City - Markus Michael Müller (Brazilian Political Science Review, 2010)
This article addresses the relationship between the privatization of security and the State in contemporary Mexico City. By presenting an analysis of the development of the local private security market, its regulatory framework and the problems stemming from inefficient enforcement of legal standards, it demonstrates that private security in Mexico City is not beyond the State. Rather, through formal and informal practices, the local state and its public security agencies play a central role within the recent transformations of local security provision.